Effect of pH on whey protein separation using high performance tangential flow filtration - Siti Hazwani, Tahir (2010)
High-performance tangential flow filtration (HPTFF) is an emerging technology that enables the separation of proteins with similar size. Optimization the pH of whey solution has a significant impact on the sieving behavior of proteins in HPTFF systems. The purpose of this research was to separate protein component, especially for -lactalbumin and -lactoglobulin from whey using HPTFF. It was operate at different pH value which is from pH 2 to pH 6. HPTFF experiment was performed using a 30 kDa polyethersulfone membrane in KvickLab filtration system. In this research, the best whey separation was occurr at pH 5 because of higher optimization the yield of β Lactoglobulin (β-Lag) in permeate stream. pH was affect the charge and the size of the protein in the whey. The ability of HPTFF to separate and purify each single protein component from whey protein will added the value of specific protein compare to its original mixture.